An Educational Pocket Book Using the ADDIE Model to Improve Parents' Understanding of Their Role in Early Childhood Gadget Use - Desni Yuniarni (Universitas Pendidikan Ganesha, 2025)
The increasing prevalence of gadget use among young children presents challenges for parents in managing time, content, and its impact on child development. Lack of knowledge and practical guidance for parents leads to inappropriate mentoring patterns. This study aims to develop an educational pocketbook for parents to guide young children in using gadgets wisely. This research is a Research and Development (R&D) study using the ADDIE model. The subjects were two expert validators (a psychologist and a PG-PAUD lecturer) and 40 parents of young children (10 small trials, 30 large trials). Data were collected through interviews, expert validation questionnaires, and user response questionnaires, and analyzed descriptively, quantitatively, and qualitatively. The validation results show the pocketbook is categorized as